Sustainability Analysis of Business Community Mentoring and Training Program to Increase the Business Scale of its Members - Gunawan Gunawan; Luki Adiati Pratomo (International Journal Labs, 2023)
The SDGs (Sustainable Development Goals) have 169 targets, 319 indicators, and 17 goals starting from 2015 to 2030. Of the 17 sustainable development goals, one of the SDGs (Sustainable Development Goals) that has received the most attention to date is poverty. This is because all of the SDG’s goals are a form of encouragement and effort to achieve the target of